Design of BPM Processes in Higher Education in Ecuador - Molina-Izurieta, Rosa (2023)
Introduction: This manuscript addresses the strategy for digital transformation in university management as an improvement for the development of the link with society, where the digital transformation strategy for the Academy in Ecuador is taken as a reference. Objective: To design the planning sub-process through a Business Process Management Suite as a proposal for improvement in the Information Technology degree programme at the University of Guayaquil. Method: To carry out the design proposal for automation, the problem definition, the AS-IS model, the Hammer PEMM diagnosis for the company and processes are presented. The model is optimised based on the process mining analysis to obtain the TO-BE process. For the implementation, the database, formats, and the end-user interface are designed. Together with the ROI estimation for the justification of the feasibility of the proposal. Results: With the TO-BE process optimised by a business process analysis (BPA) software package, a time reduction of 51% and a total cost reduction of 41% is achieved. The estimated return on investment (ROI) is 1.61. Conclusion: Optimisation through process mining increases the assertiveness in the design of the proposal, exceeding even the initial projection of optimising the process by 30% in contrast to the 51% obtained. The estimated return on investment facilitates the justification for technical implementation, according to the institutional investment programme.